Intensity of Social Media Use on Anxiety Level of Preclinic Students, Faculty of Medicine, Muslim University of Indonesia - Ismail, Muhammad Wirasto; Liaury, Kristian (Journal of Community Health Provision, 2024)
Social media, which was originally created to facilitate communication and strengthen relationships between individuals, sometimes has a negative impact. Several factors have contributed to the increase in symptoms. anxiety and decreased individual well-being, such as increased time spent on sites, comparing social status, receiving negative feedback, posting related news stress, and feelings of being under pressure. Research Objectives This to determine the intensity of social media use on the anxiety level of preclinical students of the Faculty of Medicine. The sample in this study were participants in the Medical Education Program of the Faculty of Medicine, Muslim University of Indonesia. The research subjects then filled in questionnaire that has been given in the form of Google Form. The collected data was processed and analyzed using SPSS 23. The results of the study show that the distribution of respondents' answers and the variable correlation test obtained a p value (0.003) <0.05, which means that there is a correlation between SNAIS and GAD with an r value of 0.225. Thus, according to the hypothesis, the higher the intensity of social media use, the higher the anxiety. Based on results Research There is a significant correlation between GAD and SNAIS scores, so the higher the intensity of social media use, the higher the anxiety.